Martin Rivas - Blest Gana, Alberto, 1830-1920 (Edición Digital, 2013)
This is the story of a youngster who is entrusted to the household of a member of the Santiago elite. While living there he falls in love with his guardian's daughter, and their love provides a commentary about the mores of Chilean society.